2023
DOI: 10.25100/socolen.v49i1.11487
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable control measures of IPM of the cereal leafminer Syringopais temperatella Led. (Lepidoptera: Scythrididae): Short-term effect of tillage system

Abstract: Syringopais temperatella Led. (Lep., Scythrididae) is a serious threat of barley and wheat in Jordan as it causes a great loss in crop. There is a growing interest in the development of innovative control strategies aiming to minimize the environmental impact of pest management and improve the safety of the agro-food chain. However, little attention has been paid on the use of cultural control methods against the pest, accordingly, this study aimed at investigating the effect of tillage system in controlling S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Tillage involves manipulation of the soil into a desired condition by mechanical means such as digging, stirring, and overturning for planting and cultivation. However, the benefits of tillage could be temporary as long-term studies have shown degradation of soil structure, compaction, erosion of top soil, and extinction of soil-dwelling fauna as some of the consequences of it (Bhardwaj et al, 2016;Singh et al, 2020;Dey and Karmakar, 2021;Ghabeish et al, 2023). Other consequences of persistent use of conventional farming practices include depletion of natural resources (Kakraliya et al, 2018), biodiversity loss (Shaxson et al, 2008), environmental pollution (Stevens et al, 2012), and human health hazards (Nderitu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tillage involves manipulation of the soil into a desired condition by mechanical means such as digging, stirring, and overturning for planting and cultivation. However, the benefits of tillage could be temporary as long-term studies have shown degradation of soil structure, compaction, erosion of top soil, and extinction of soil-dwelling fauna as some of the consequences of it (Bhardwaj et al, 2016;Singh et al, 2020;Dey and Karmakar, 2021;Ghabeish et al, 2023). Other consequences of persistent use of conventional farming practices include depletion of natural resources (Kakraliya et al, 2018), biodiversity loss (Shaxson et al, 2008), environmental pollution (Stevens et al, 2012), and human health hazards (Nderitu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…RAPD is considered adequate genotype identification and analysis of genetic differences among induced mutants (Wahyudi et al 2020). In addition to Heliconiaceae and Streltiziceae, RAPD has been popularly applied at inter-and intra-specific levels of various plant species, such as wheat and barley (Ghabeish et al, 2021), rice (Sholikhah et al, 2019), ramie (Mayerni et al, 2019), legumes (Purwanti et al, 2021), pea (Osman and Ali, 2021), orchid (Hartati and Samanhudi, 2022), kalanchoe (Al-Khayri et al, 2022), banana (Probojati et al, 2019;Wiguna and Pharmawati, 2021), ginger (Trimanto et al 2023), and many more. RAPD is a DNA amplification technique based on PCR using random primers and generally consists of 10 arbitrary base sequences with a minimum content of G and C bases of 60%.…”
Section: Introductionmentioning
confidence: 99%